THE ROLE OF PIANO PIECES IN KODÁLY’S LIFE - DOMBI, Erzsébet Józsefné (Studia Universitatis Babes-Bolyai Musica, 2023)
This study summarizes the composer’s piano works for the occasion of Kodály’s 140th anniversary. It introduces the role of the piano in Kodály’s life, the works he became acquainted with during his studies, and whether he had the opportunity to perform them in concert during his lifetime. Other questions include which study trips could have influenced the composition of his piano pieces, in which period were the piano pieces written, and who were the performers of the first performances. The research method is documentary analysis. As a result of the research, it can be concluded that Kodály had no formal piano teacher. He acquired his knowledge through lessons from his sister. He was driven by curiosity to become acquainted with all of Bach’s Well-Tempered Clavier. He later used the instrument in his composing. We also found examples of him accompanying his songs in concerts. The piano pieces were influenced by his study trip to France. The piano pieces were composed in 3 periods.